Emperor Qianlong's hidden treasures. : reconsidering the collection of the Qing imperial household - Chiang, Nicole T. C. (Hong Kong University Press, 2019)
In this stunning reassessment, Nicole T.C. Chiang argues that the famous Qianlong art collection is really 'the collection of the imperial household in the Qianlong reign'. The distinction is significant because it strips away the modern, Eurocentric preconceptions that have led scholars to misconstrue the size of the collection, the role of nationalism in its formation, the distinction between art and artifact, and the actual involvement of the emperor in assembling the collection. No one interested in Chinese art will be able to ignore the ramifications of this important study. Emperor Qian.